2015
DOI: 10.1073/pnas.1416531112
|View full text |Cite
|
Sign up to set email alerts
|

Evolution of the rapidly mutating human salivary agglutinin gene ( DMBT1 ) and population subsistence strategy

Abstract: The dietary change resulting from the domestication of plant and animal species and development of agriculture at different locations across the world was one of the most significant changes in human evolution. An increase in dietary carbohydrates caused an increase in dental caries following the development of agriculture, mediated by the cariogenic oral bacterium Streptococcus mutans. Salivary agglutinin [SAG, encoded by the deleted in malignant brain tumors 1 (DMBT1) gene] is an innate immune receptor glyco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
57
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
3
2

Relationship

3
6

Authors

Journals

citations
Cited by 38 publications
(60 citation statements)
references
References 53 publications
3
57
0
Order By: Relevance
“…To validate the computational callsets, we used: aCGH; alkaline lysis fibre-FISH, following the protocol of Perry, et al 42 ; and molecular combing fibre-FISH, following Polley et al 43 , Carpenter et al 44 , and instructions from the manufacturer, Genomic Vision.…”
Section: Methodsmentioning
confidence: 99%
“…To validate the computational callsets, we used: aCGH; alkaline lysis fibre-FISH, following the protocol of Perry, et al 42 ; and molecular combing fibre-FISH, following Polley et al 43 , Carpenter et al 44 , and instructions from the manufacturer, Genomic Vision.…”
Section: Methodsmentioning
confidence: 99%
“…Microbial-host coevolution may not only affect the structure of glycans, but also their numbers, densities, and sterical presentations on their protein or lipid backbone, and perhaps in a larger sense on any cell or biological surface [102]. An example for that effect may be the observed variations in the number of densly O-glycosylated PTS repeat domains in salivary agglutinins [103] and mucins [104, 105] which are known to interact with microbes through glycan-mediated binding (sections 3.1 and 3.2 ). For example, variations in subexonic PTS copy number repeats in salivary mucin MUC7 underwent rapid evolution in the primate lineage and among other mammalian species [59], and similar mechanisms involving possible pathogenic pressure may explain the observable variations in MUC7 among geographically distinct human populations [58].…”
Section: Evolution and Coevolution Of Host Glycans And Microbes In The mentioning
confidence: 99%
“…Given their larger size, an individual SV potentially has a higher phenotypic impact than single nucleotide variants, especially when affecting functional sequences (Conrad et al 2009;Iskow et al 2012aIskow et al , 2012b. In fact, SVs have been associated with many human diseases (Weischenfeldt et al 2013), especially autoimmune, metabolic and cognitive disorders (Polley et al 2015;Hollox et al 2008;Stefansson et al 2008;Traherne et al 2010). However, the haplotype architectures around SVs are generally complex due to repeat content, gene conversion and recurrent formation of SVs, making it difficult to accurately impute them in genome-wide association studies (Sudmant et al 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, previous studies have shown a drastic depletion of deletion polymorphisms from exonic regions (Conrad et al 2009). Despite the overall depletion of SVs in functional sequences, there are still some SVs that are passively tolerated under relaxed negative selection (Nguyen et al 2008;Eaaswarkhanth et al 2016), and some others that are actively maintained by non-neutral evolutionary forces (Gokcumen et al 2013b;Pajic et al 2016;Perry et al 2007;Polley et al 2015).…”
Section: Introductionmentioning
confidence: 99%